(untitled) (Al-Mufassir: Jurnal Ilmu Alquran, Tafsir dan Studi Islam, 2022)
Every letter in the Qur’an has a purpose, including the letter al-Muzzammil. According to Wahbah Az-Zuhaili in Tafsir Al-Munir, explained that Surah Al-Muzammil as a letter that was revealed in the early days of Islam consisting of 20 verses contains three themes, each of which contains spiritual values. Through Maqashidi analysis, these values are maqashid surah which includes maqashid Tawhid, worship, sincerity, humility, patience, and morality. The maqashid became the initial provision for Muslims in the early days of Muhammad’s apostleship as a universal value that guided the life of Muslims from the time of the Companions to the end of time.